Molecular mapping of genomic regions and identification of possible candidate genes associated with gynoecious sex expression in bitter gourd - N. D., Vinay; Matsumura, Hideo; Munshi, Anilabha Das; Ellur, Ranjith Kumar; Chinnusamy, Viswanathan; Singh, Ankita; Iquebal, Mir Asif; Jaiswal, Sarika; Jat, Gograj Singh; Panigrahi, Ipsita; Gaikwad, Ambika Baladev; Rao, A. R.; et al. (Frontiers in Plant Science, 2023)
Bitter gourd is an important vegetable crop grown throughout the tropics mainly because of its high nutritional value. Sex expression and identification of gynoecious trait in cucurbitaceous vegetable crops has facilitated the hybrid breeding programme in a great way to improve productivity. In bitter gourd, gynoecious sex expression is poorly studied and detailed molecular pathways involved are not understood. The present study was conducted to elucidate the inheritance, identify the genomic regions associated with gynoecious sex expression and to reveal possible candidate genes through QTL-seq. Segregation for the gynoecious and monoecious sex forms in the F2 progenies indicated single recessive gene controlling gynoecious sex expression in the genotype, PVGy-201. Gynoecious parent, PVGy-201, monoecious parent, PDM, and two contrasting bulks were constituted for deep-sequencing. A total of 10.56, 23.11, 15.07, and 19.38 Gb of clean reads from PVGy-1, PDM gynoecious bulk and monoecious bulks were generated. Based on the ΔSNP index, 1.31 Mb regions on the chromosome 1 was identified to be associated with gynoecious sex exporession in bitter gourd. In the QTL region 293,467 PVGy-1 unique variants, including SNPs and indels, were identified. In the identified QTL region, a total of 1019 homozygous variants were identified between PVGy1 and PDM genomes and 71 among them were non-synonymous variants (SNPS and INDELs), out of which 11 variants (7 INDELs, 4 SNPs) were classified as high impact variants with frame shift/ stop gain effect. A set of twelve genes associated with male and female gametophyte development were identified in the QTL-region. Ethylene-responsive transcription factor 12, Auxin response factor 6, Copper-transporting ATPase RAN1, CBL-interacting serine/threonine-protein kinase 23, ABC transporter C family member 2, DEAD-box ATP-dependent RNA helicase 1 isoform X2, Polygalacturonase QRT3-like isoform X2, Protein CHROMATIN REMODELING 4 were identified with possible role in gynoecious sex expression. The findings in the study provides insight about sex expression in bitter gourd and will facilitate fine mapping and more precise identification of candidate genes through their functional validation.